ANALISIS SISTEM PENGENDALIAN INTERN TERHADAP PENGELOLAAN PIUTANG PADA AMANAH FINANCE CABANG GORONTALO - Latif, Abdul; Solang, Yuningsih Van (Li Falah: Journal of Islamic Economics and Business, 2016)
This study aimed to analyze the implementation of the internal control system covering quality employees in accordance with their responsibilities. The separation of responsibilities properly and periodically comparison to Amanah Finance receivables management in Gorontalo branch. This type of approach of this research is descriptive research type. This study found that the internal implementation of internal control processes are already running with less good, because the management has done a separation of responsibility on each employee based on the competence of each employee and has done secarah full delegation of authority. Each recording transactions authorized by the accounts receivable function of cash receipts and disbursements. Then, at the end of each period selau made adjusting entries, and financially prepared financial statements on a regular basis. The management of Finance to evaluate periodically based on financial statements prepared in each period.